2022
DOI: 10.1111/jop.13325
|View full text |Cite
|
Sign up to set email alerts
|

Decoding a gene expression program that accompanies the phenotype of sporadic and basal cell nevus syndrome‐associated odontogenic keratocyst

Abstract: Background: Odontogenic keratocyst is characterized by local aggressive behavior and a high recurrence rate, as well as its potential to develop in association with the basal cell nevus syndrome. The aim of this study was to decode the gene expression program accompanying odontogenic keratocyst phenotype.Methods: 150-bp paired-end RNA-sequencing was applied on six sporadic and six basal cell nevus syndrome-associated whole-tissue odontogenic keratocyst samples in comparison to six dental follicles, coupled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 31 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…The vast majority of studies (24 out of 29) reported experiments on FFPE tissue samples ( Table S3 ), two studies included both fresh-frozen and FFPE samples [ 6 , 39 ], one study reviewed only fresh-frozen samples [ 42 ], and in vitro analysis of human odontogenic lesion-derived cells was performed in two studies [ 43 , 47 ]. A minority of studies (10 out of 29) documented the microscopic diagnosis of included odontogenic entities, either by providing a detailed microscopic description [ 6 , 11 , 12 , 29 , 35 ] or by mentioning an appropriate reference [ 13 , 32 , 36 , 37 , 39 ], e.g., the WHO 2017 [ 1 ] or 2005 [ 51 ] editions for odontogenic tumors and cysts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of studies (24 out of 29) reported experiments on FFPE tissue samples ( Table S3 ), two studies included both fresh-frozen and FFPE samples [ 6 , 39 ], one study reviewed only fresh-frozen samples [ 42 ], and in vitro analysis of human odontogenic lesion-derived cells was performed in two studies [ 43 , 47 ]. A minority of studies (10 out of 29) documented the microscopic diagnosis of included odontogenic entities, either by providing a detailed microscopic description [ 6 , 11 , 12 , 29 , 35 ] or by mentioning an appropriate reference [ 13 , 32 , 36 , 37 , 39 ], e.g., the WHO 2017 [ 1 ] or 2005 [ 51 ] editions for odontogenic tumors and cysts.…”
Section: Resultsmentioning
confidence: 99%
“…All but one of the retrieved studies reported the expression of stem cell markers in odontogenic tumors and cysts based on immunohistochemical or immunofluorescence analyses ( Table 1 ). One study used flow cytometry to compare the expression of stem cell markers in cells derived from odontogenic cysts and dental pulp stem cells [ 43 ], two studies confirmed the expression of stem cell markers via reverse transcription-PCR (RT-PCR) and immunohistochemistry [ 13 , 47 ], and two studies employed advanced molecular biology methods, i.e., microarrays on fresh-frozen samples [ 42 ] and RNA-seq on FFPE tissues [ 37 ], and validated their results via RT-PCR and/or immunohistochemistry/immunofluorescence. Tables S4 and S5 present detailed information regarding the immunohistochemistry/immunofluorescence experiments and the other techniques, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 , 6 However, there was no significant difference between sporadic OKC and GS among mutations in the PTCH1 , proliferating markers such as proliferating cell nuclear antigen (PCNA), Ki-67, and p53 expression, as well as broad-spectrum transcriptomic features. 33 36 And so far, there is no clear method of identification when there was no clinical manifestations except OKC at the early stage of GS. OOC is a relatively uncommon odontogenic developmental cyst, and was previously classified as belonging to OKC.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between OKC and GS is strengthened by numerous correlations, such as similar PTCH1 mutations and gene expression profiles, resulting in the confusion tendency. 34 , 36 , 47
Fig. 6 The workflow of artificial intelligence models development.
…”
Section: Discussionmentioning
confidence: 99%